Total phenolic contents and free radical scavenging capacity of clitoria ternatea (bunga telang) extract - Haron, Normah; Mat Jusoh, Hanapi; Ali, Siti Shahirah (2019)
Introduction: Most parts of Clitoria ternatea have been investigated for their medicinal purposes such as antimicrobial, antioxidant, anti-diarrheal, anti-diabetic, treatment for skin disease, sore throat, and memory enhancement. The present study aimed to investigate the total phenolic contents in free and bound forms (soluble and insoluble bound) and their radical antioxidant scavenging capacity. Methods: Free phenolic extract was acquired through direct methanol extraction while acidic and alkaline hydrolyses were adopted to release the bound phenolic. The total phenolic content (TPC)s were determined using Folin-Ciocalteu assay and expressed in gallic acid equivalents (GAE). The fractions were evaluated for their antioxidant capacity using DPPH assay. Results: The highest phenolic content was found in insoluble bound extract followed by soluble bound and free extracts (1.87 ± 0.05, 1.63 ± 0.05, 1.05 ± 0.11 mg GAE/ g DW, respectively). At the highest concentration of 50 mg/ml, soluble bound extract demonstrated the highest radical scavenging capacity compared to insoluble bound and free extracts (84.24 ± 1.96 %, 83.49 ± 1.03 %, and 63.37 ± 5.33 %). Conclusions: The insignificant differences between all the extracts and antioxidant inhibition in this present study suggested that different forms of extracts did not influence the radical scavenging capacity.